ANATOMY OF AN ETHNIC GROUP: SOCIAL AND RELIGIOUS LIFE IN DİYARBAKIR ZAZAS (YAZYAĞMURU AND ÇATALDUT VILLAGES CASE) - Cemile Zehra KÖROĞLU (Fırat University, 2019)
This study is a field survey carried out on the Zazas which are ethnic groups surviving in the Southeastern Anatolia Region of Turkey. This is a district of Diyarbakır Province where Çüngüş live in mountain villages, Yazyağmuru and Çataldut. While there are studies on Alawi Zazas living in the region of such as Dersim, Siverek, Bingöl, there is no study built on the Sunni Zazas. For this reason, the research has the distinction of being the first in its area. Consisting of total field under survey of the research on villages which have ethnic characters, the research refers primarily to the branches of sociology such as Rural Sociology and Ethnic Sociology. However, the study mainly is a religious life research which was carried out in the Department of Sociology of Religion. In this sense, as well as social and cultural life of Çataldut and Yazyağmuru Villages, basing on faith and worship dimensions of religious life, with the customs and practices concerning transition period, the position of religion in these practices were tried to examine in all aspects of the research. The research is not only a field study based on a survey, but also a projecte developed for over a participation life in the region which is the subject of the research. This gives us an opportunity of collecting data profoundly concerning all dimensions of cultural life. Altough the research is on an ethnic group, it is identified that elements based on ethnic differences do not lead to a different identity demand. In this sense, the researched ethnic group is able to form channels which connect itself to the social totality. In this respect, it is possible to refer to the phenomenon of migration and institution of religion which play important roles. The research also depicts social and religious life which attempts to channel areas which are embedded in social and cultural structures and supplying connection with the social totality.